Réponses

2014-06-01T19:35:55+02:00
H=(5x+1)²-(5x+1)(x-6)
1.H=(5x+1)(5x+1-x+6)
H=(5X+1)(4x+7)
2.H=20x²+35x+4x+7
H=20x²+39x+7
4.H=(5x+1)(4x+7)   [x=√3]
H= (5√3+1)(4√3+7)
H=60+35√3+4√3+7
H=39√3+67
2014-06-01T19:38:17+02:00
1)
H=(5x+1)²-(5x+1)(x-6)
  =(5x)²+2*5x*1+1²-(5x*x+5x*(-6)+1*x+1*(-6))
  =10x²+10x+1-(5x²-30x+1x-6)
  =10x²+10x+1-(5x²-29x-6)
  =10x²+10x+1-5x²+29x+6
  =5x²+39x+5

2)
H=(5x+1)²-(5x+1)(x-6)
  =(5x+1)(5x+1)-(5x+1)(x-6)
  =(5x+1)(5x+1-(x-6)
  =(5x+1)(5x+1-x+6)
  =(5x+1)(4x+7)

3)
(5x+1)(7+4x)=0
Un produit est nul si et seulement si un des facteurs est nul.
5x+1=0
5x=-1
x=-1/5
ou
7+4x=0
4x=-7
x=-7/4

4)
H=5x²+39x+5
  =5*V3²+39*V3+5 
  =5V3+39V3+5
  =44V3+5

voilà :)